First GEM measurements at WEST and perspectives for fast electrons and heavy impurities transport studies in tokamaks. (1st January 2022) - Mazon, D.; Chernyshova, M.; Jardin, A.; Peysson, Y.; Król, K.; Malard, P.; Czarski, T.; Wojeński, A.; Malinowski, K.; Colette, D.; Poźniak, K.T.; Kasprowicz, G.; et al.
Abstract: Soft X-ray (SXR) radiation emitted from tokamak plasmas contains very useful information about plasma stability, shape and impurity content, all key parameters to improve plasma performance. In the deuterium-tritium phase of ITER, the high neutron fluxes, gamma and hard X-ray emission will constitute too harsh an environment to permit the use of classical semiconductor detectors. New SXR detector technologies, more robust to such environments, should thus be investigated. First GEM (Gas Electron Multiplier) measurements performed at WEST were successful and showed that both spatially and spectrally resolved calibrated data could be acquired. Strategies to reconstruct tungsten (W) impurity radiation synthetic diagnostics, modelling and real measurements based on multiple diagnostics are proposed.